Towards Interoperable Research Infrastructures for Environmental and Earth Sciences A Reference Model Guided Approach for Common Challenges - Zhao, Zhiming; Hellström, Margareta (Lecture Notes in Computer Science; Information Systems and Applications, incl. Internet/Web, and HCI, 2020)
This open access book summarises the latest developments on data management in the EU H2020 ENVRIplus project, which brought together more than 20 environmental and Earth science research infrastructures into a single community. It provides readers with a systematic overview of the common challenges faced by research infrastructures and how a 'reference model guided' engineering approach can be used to achieve greater interoperability among such infrastructures in the environmental and earth sciences. The 20 contributions in this book are structured in 5 parts on the design, development, deployment, operation and use of research infrastructures. Part one provides an overview of the state of the art of research infrastructure and relevant e-Infrastructure technologies, part two discusses the reference model guided engineering approach, the third part presents the software and tools developed for common data management challenges, the fourth part demonstrates the software via several use cases, and the last part discusses the sustainability and future directions.